What we kept to ourselves ebook A novel. - Kim, Nancy Jooyoun (2023)
A "propulsive and moving story of a family torn asunder by their mother's disappearance" ( Bookreporter ) from the New York Times bestselling author of The Last Story of Mina Lee . 1999: At the end of the millennium, the Kim family is struggling to move on after their mother, Sunny, vanished a year ago. Sixty-one-year-old John Kim feels more isolated from his grown children than ever before. One evening, their fragile lives are further upended when John finds the body of an unhoused stranger in the backyard with a letter to Sunny, leaving the family with more questions than ever. 1977: Newly married, Sunny is pregnant and has just moved to Los Angeles from Korea with her hardworking and often-absent husband. America is not turning out the way she had dreamed it to be, and the loneliness and isolation are broken only by a fateful encounter with a veteran at a bus stop. The unexpected connection spans decades and echoes into the family's lives in the present as they uncover devastating secrets that put not only everything they thought they knew about their mother but their very lives at risk. Both "an intricately crafted mystery and a heart-wrenching family saga" (Michelle Min Sterling, New York Times bestselling author), set against the backdrop of social unrest and Y2K, What We Kept to Ourselves masterfully explores memory, storytelling, forgiveness, and what it means to dream in America.